An unusual association of disseminated staphylococcal infection in dengue fever (Indian Journal of Case Reports, 2021)
Dengue fever is an important mosquito-borne disease with a highly variable clinical spectrum, ranging from self-limiting mild illness to expanded dengue syndrome (EDS). While the immune-pathogenesis of dengue virus (DENV) infection had been studied thoroughly, the exact mechanism remains elusive. The transient suppression of host innate immunity by DENV might be the likely reason for dengue-associated co-infections and/or superinfections. In addition, the dual infection can worsen the clinical outcome of Dengue fever. We are reporting a case of disseminated staphylococcal infection in a 31-year-old healthy male with a recent dengue infection. Blood culture showed methicillin-sensitive Staphylococcus aureus. Selective IgM deficiency has been proved in this patient, which might explain, the occurrence of disseminated staphylococcal septicemia. This case report highlights the importance of early detection of atypical features and the emerging entity called EDS